Hyperimmune Globulin for Severely Immunocompromised Patients Hospitalized With Coronavirus Disease 2019: A Randomized, Controlled Trial. (4th August 2022) - Huygens, Sammy; Hofsink, Quincy; Nijhof, Inger S; Goorhuis, Abraham; Kater, Arnon P; te Boekhorst, Peter A W; Swaneveld, Francis; Novotný, Věra M J; Bogers, Susanne; Welkers, Matthijs R A; Papageorgiou, Grigorios; Rijnders, Bart J; et al.
Abstract: Background: The aim of this randomized, controlled trial is to determine whether antisevere acute respiratory syndrome coronavirus 2 hyperimmune globulin (COVIG) protects against severe coronavirus disease 2019 (COVID-19) in severely immunocompromised, hospitalized, COVID-19 patients. Methods: Patients were randomly assigned to receive COVIG or intravenous immunoglobulin (IVIG) without SARS-CoV-2 antibodies. Results: Severe COVID-19 was observed in 2 of 10 (20%) patients treated with COVIG compared to 7 of 8 (88%) in the IVIG control group ( P = .015, Fisher's exact test). Conclusions: Antisevere acute respiratory syndrome coronavirus 2 hyperimmune globulin may be a valuable treatment in severely immunocompromised, hospitalized, COVID-19 patients and should be considered when no monoclonal antibody therapies are available. Abstract : Anti-SARS-CoV-2 hyperimmune globulin (COVIG) could be a therapy for severely immunocompromised, hospitalized, COVID-19 patients. We performed a randomized, placebo-controlled trial in which a single intravenous infusion with 15 grams of COVIG significantly reduced the progression to severe COVID-19.